INTERNATIONAL ORGANIZATIONS AS A TOOL FOR THE DEVELOPMENT OF THE WORLD ECONOMY - ZAHORODNIA, Alona (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores the genesis and development of the world economy, its stages of formation and the role of international organizations in this process. The interrelationships between the formations of the light dominion, the regional capitals and the international scientific tradition have been analyzed. Particular respect is given to the key historical stages in the development of the world economy: from the era of geographical innovations to the current period of the global market. The activities of the main international organizations, such as the UN, IMF, UNCTAD, WTO, are examined, their role in stabilizing the economy, supporting powers in times of crisis and global conflict economical integration. The key concepts that underpinned the development of international organizations since the XIX’th century, with the emergence of international conferences, committees and the first inter-governmental organizations, have been identified. Particular respect is given to the changes in international economic sectors after the Second World War, as well as the influx of globalization and integration processes into the formation of the current mechanism management of the light economy. The statistics also emphasize that international organizations have become important instruments for conflict regulation, development and promotion of international standards in trade, protection of human rights and other middle During the analysis of the mechanisms for regulating international economic transport, the emphasis is placed on the need for modernization to counter current global pressures, including economic unevenness, climate change and safety. It is agreed that international organizations have become an important tool for regulating the world economy, dealing with the most pressing global problems, coordinating economic policy and developing international trade. The prospects for further research focus on the detailed mechanisms of regulation of the world economy in the context of current global crises. A comprehensive analysis of the formation and development of the world economy in the context of interaction with international organizations has been carried out. The role of international cooperation in the newly formed model of economical containers has been revealed, as it has passed through several stages: from regional connections to global integration.